Annual Reviews of Computational Physics IX - Stauffer Dietrich (World Scientific, 2001)
The 9th volume of "Annual Reviews of Computational Physics" has as a special feature a comprehensive compendium of interatomic potentials as used for materials properties. Other articles deal with simulations of magnetic nanostructures, improved Monte Carlo methods (eg. for nucleation studies in Ising models), fluid dynamics with large mean free paths, the growing field of "sociophysics", and teaching of undergraduate computational physics (including an introduction to Java).